Peningkatan Kemampuan Guru Pada Penerapan Model Pembelajaran Take and Give Dalam Pembelajaran Melalui Pembinaan Kepala Sekolah: Improving Teacher Ability in the Application of Take and Give Learning Models in Learning through Principal Coaching - Agustinus Waruwu (CERED Indonesia Publishing, 2022)
School Action Research has the aim of increasing the ability of subject teachers to use the Take and Give Learning Model in subjects taught in junior high schools. Research respondents were teachers of SMP Negeri 2 Ma'u, totaling 13 people. The research instrument used a written evaluation sheet, to be used in each cycle. The study was conducted in two cycles with several meetings between the principal and participants to receive coaching using the Take and Give Learning Model. According to the Principal's data on the participants' initial ability to master the Take and Give Learning Model at a low average level of around 44.61 then the principal's coaching actions in the first cycle experienced an increase in the mastery of the participants' abilities to an average of 61.53, this level is still far from the expectations of the Principal, then continued with the second cycle of action then evaluated the ability of the participants with an average result of 80. It turns out that through repeated coaching actions to introduce new things to teachers will be able to increase the ability of teachers in implementing the Take and Give Learning Model in lesson.